Moderate Da'wah and National Resilience: A Case Study at the Bandung Regency Religious Harmony Forum (FKUB) - Solahudin, Dindin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
This study tries to offer constructive preaching to build national resilience by highlighting Islamic moderation (wasaá¹iyyatul Islam) through a series of moderate daâ€™wah. This research was conducted through a qualitative approach using the case study method on a series of activities carried out by the Bandung Regency Religious Harmony Forum (FKUB) to build a spirit of tolerance, moderation and national harmony. Research data were collected through observation techniques, interviews, documentation, and literature study. The results of the study concluded that wasaá¹iyyatul IslÄm is an authentic character of Islamic law that reflects i'tidÄl (perpendicularity) and istiqÄmah (consistency) in aá¹£-á¹£irÄth al-mustaqÄ«m (straight path). Islam is moderate as long as it is understood in the corridor of truth. Islam, with its wasaá¹iyyah nature, should also be preached mildly. MuqÄbalah moderation is not radicalism but extremity. Radical da'wah is not a problem as long as istiqÄmah is in the corridor of moderation. Preaching radically moderate Islam is certainly not justified. Extreme da'wah undermines Islamic moderation and contradicts Islamic law itself. Islamic moderation necessitates its adherents to practice Islamic law moderately. Moderate da'wah socializes Islam to be practised by its followers mildly. Religious moderation is an essential social capital for national resilience. FKUB Bandung Regency has a strategic role in building spiritual awareness in an emancipatory manner, empowering religious communities in a participatory way, building collective and collaborative partnerships, and formulating transformative diversity dialogues. Thus, the existence of FKUB in Bandung Regency can be seen as a social entity that impacts building a spirit of moderate da'wah to realize a religious ecosystem that strengthens national resilience.